Data‐driven virtual power plant bidding package model and its application to virtual VCG auction‐based real‐time power market. Issue 5 (2nd June 2020) - Xinhe, Chen; Wei, Pei; Wei, Deng; Hao, Xiao
Abstract : Energy storage and virtual power plant technologies have been developed and become important technical means to enhance power system stability and reduce real‐time dispatching costs. In this study, the dispatching capability and dispatching cost characteristics of the virtual power plants are analysed firstly in detail, as well as the dispatching difficulties under the traditional market modes. Hence, virtual power plant real‐time bidding package model and virtual auction‐based real‐time power market mechanism are proposed. Data‐driven virtual power plant real‐time packing method and bidding package model integrated virtual Vickrey–Clarke–Groves auction model are put forward. Finally, the feasibility and validity of the proposed mechanism and method are verified by case studies and result in analyses of the IEEE‐30 bus test system with multiple virtual power plants, providing a scientific foundation and a practical solution to the real‐time power market.